Os impactos da reestruturação produtiva de uma grande empresa siderúrgica sobre o mercado de trabalho local - Simone de Souza; Antonio Carvalho Neto (Ciências Sociais Unisinos)
This article discusses the process of the production restructuring in the Brazilian steel mill sector during the 1990s and its impact on the local labor market. The rapid falling of commercial barriers associated with economic stability forced national corporations to build new competitive advantages. Corporations intensified production restructuring during these years in order to ensure quality, productivity and cost reduction by adopting technological and organizational innovations. These transformations inspired by the Japanese model impacted on the labor market. This article analyzes the impact of the production restructuring of USIMINAS, the largest steel mill company in the state of Minas Gerais, on the local labor market in the city of Ipatinga. It is based on data from the Brazilian Labor Ministry and from USIMINAS and associates the period of the company¿s privatization and production restructuring with these data. Its results show a reduction of the company¿s share in the local labor market and an increase in the sector of services. The level of school education required by the company was raised, but wages went down. Younger workers (18 to 29 years o age) predominate over against older ones (30 to 39 years). The number of workers of contracted companies increased and the number of those hired directly by USIMINAS decreased.